Comparison between solar thermal steam turbine and photovoltaic system in efficiency and cost - Li, Shilin. (2010)
Energy and environment are two of the most concerning issues in the current world. Today electricity is generated by consuming mainly fossil fuels such as coal, oil and natural gas. Not only the fossil fuels are limited but also their emissions have serious negative impacts on our environment such as adding to the greenhouse effect and causing acid rain. To reduce the amount of the fossil fuels consumption while supply the sufficient power to meet the increasing demand is a tough task. As a clean, free, and non-consuming source, solar energy utilization is getting more and more attention. There are two approaches using solar energy to generate electricity. One is the photovoltaic (PV) and another one is solar thermal energy plant. This thesis investigates the efficiency of the two approaches and link with design tools. The solar thermal energy plant is combined with the stearn turbine to generate electricity. This approach is suitable for the large scale of plants which need large rural area for the installation. Photovoltaic plant can be in large or small scale and is more common installed in the residence area. A comparison between the two kinds of solar aided generation systems in cost is also roughly discussed. With the increase of PV connected to conventional power grids, the impact of the PV on the grid cannot be ignored. A simulation method is needed to analyze the effect of the PV on the grid. MATLAB/SIMULINK is used to analyze the effect of PV panels on an power system.